PENDAMPINGAN PENULISAN KARYA ILMIAH (KIR) SISWA MAN SE-KABUPATEN BONDOWOSO - Suheri (Institut Agama Islam Tribakti Kediri, 2023)
The objectives of this assistance are: Improving the quality/quality of writing scientific papers for students so that they are in accordance with scientific principles in reputable journals, Strengthening competence in scientific research to convey certain ideas through identification, literature review and methodology, Strengthening students' competencies in the field of writing works scientific and digital literacy, and improve research results and KIR writing results at MAN Bondowoso. the results of the activity stated that if the Teacher and students considered the Assistance Activities for Writing Scientific Papers (KTI) at MAN Bondowoso this was very necessary in developing students' journalistic abilities and digital literacy, especially in writing scientific papers. This Scientific Writing (KTI) writing assistance activity received a good response from the institution, teachers and participants. The enthusiasm of the participants was very high in participating in this workshop. This can be seen from the attendance rate of nearly 80% of the participants and the many questions asked during the activity process.